2020
DOI: 10.1111/dth.14183
|View full text |Cite
|
Sign up to set email alerts
|

Long lasting facial rejuvenation by repeated placement of calcium hydroxylapatite in elderly women

Abstract: Calcium hydroxylapatite (CaHA) is a biostimulatory filler with long lasting efficacy after a single injection. Data con the effect of repeated injections, however, are sparse. This is a single-center observational study. Forty Caucasian females of Fitzpatrick skin type I to III, aged between 50 and 95 years (mean age 63 ± 13.4 years), and seeking nonsurgical improvement of facial aging were included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(56 reference statements)
0
5
0
3
Order By: Relevance
“…Preferred injection sites were NLFs (38%, n = 1,930 of 5,081 injections), marionette lines (16%, n = 815), and chin and prejowl (Table S1). [30][31][32][33][34][35][36][37][38] Overall subject satisfaction scores were high regardless of the area treated (87-89%). 36 For more than 4 years, evidence revealed that CaHA has had a favorable safety profile, high patient satisfaction, and good durability.…”
Section: Mixed Indications On the Facementioning
confidence: 99%
“…Preferred injection sites were NLFs (38%, n = 1,930 of 5,081 injections), marionette lines (16%, n = 815), and chin and prejowl (Table S1). [30][31][32][33][34][35][36][37][38] Overall subject satisfaction scores were high regardless of the area treated (87-89%). 36 For more than 4 years, evidence revealed that CaHA has had a favorable safety profile, high patient satisfaction, and good durability.…”
Section: Mixed Indications On the Facementioning
confidence: 99%
“…Por outro lado, Liu, et al, (2018) relataram um caso clínico de uma paciente de 44 anos que foi submetida a tratamento com hidroxiapatita de cálcio (Radiesse@), com o objetivo de elevar a sobrancelha, mas neste caso a paciente não percebeu nenhum efeito lift na sobrancelha como desejado. Wollina, et al, (2020) relatou um estudo com 40 mulheres entre 50 e 95 anos que receberam injeção de hidroxiapatita de cálcio (Radiesse®) e que repetiram o procedimento com 12 a 14 meses em média e foram avaliadas até 6 anos após a primeira injeção. Mulheres que tinham feito lifting cirurgico e fios não foram incluidas no estudo.…”
Section: Satisfaçãounclassified
“…Nos últimos anos, além da busca deste rejuvenescimento natural e harmonioso, muitas pessoas buscam o embelezamento no sentido de "corrigir" características faciais que não lhes são agradáveis. Para que isto aconteça, se faz necessário intervir em planos diferentes da face, uma vez que o envelhecimento é o resultado de mudanças nas cinco camadas anatômicas da face: ossos, ligamentos, músculos, tecido adiposo e pele (De Almeida, et al, 2019;Wollina, et al, 2020). Do mesmo modo, tem-se observado o aumento na busca de procedimentos não cirurgicos para tratamento de rejuvenescimento do rosto e corpo por causa do reduzido tempo de inatividade e menor chance de complicações (Guida, et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Despite the injected product has been recently shown to be safe and effective in an elderly female study population, it has to be mentioned that the adverse event described in this case report is not specific to the product administered. 15 The occurred intraarterial injection could have happened with any other injectable soft tissue volumizers f.i. hyaluronic acid based soft tissue fillers.…”
Section: Correlation To Presented Symptomsmentioning
confidence: 99%